Fully Biodegradable Airway Stents Using Amino Alcohol‐Based Poly(ester amide) Elastomers. Issue 10 (25th March 2013) - Wang, Jane; Boutin, Kyle G.; Abdulhadi, Omar; Personnat, Lyndia D.; Shazly, Tarek; Langer, Robert; Channick, Colleen L.; Borenstein, Jeffrey T.
Abstract Airway stents are often used to maintain patency of the tracheal and bronchial passages in patients suffering from central airway obstruction caused by malignant tumors, scarring, and injury. Like most conventional medical implants, they are designed to perform their functions for a limited period of time, after which surgical removal is often required. Two primary types of airway stents are in general use, metal mesh devices and elastomeric tubes; both are constructed using permanent materials, and must be removed when no longer needed, leading to potential complications. This paper describes the development of process technologies for bioresorbable prototype elastomeric airway stents that would dissolve completely after a predetermined period of time or by an enzymatic triggering mechanism. These airway stents are constructed from biodegradable elastomers with high mechanical strength, flexibility and optical transparency. This work combines microfabrication technology with bioresorbable polymers, with the ultimate goal of a fully biodegradable airway stent ultimately capable of improving patient safety and treatment outcomes.